Heuristic Analysis of the Indonesian Covid-19 Official Website Interface - Moch Yusuf Asyhari; Kelik Sussolaikah; Eka Resty Novieta Sari; Sekreningsih Nita (Indonesian Scientific Journal, 2022)
The Government of Indonesia's official Covid-19 website is the most trusted information link between relevant agencies and the wider community. Usability is an important factor in determining how easily and successfully users can obtain information from a website. Heuristic studies were conducted to obtain findings on the discrepancies in the previously released website design. The website's homepage has a usability percentage of 78.74 percent and a standard deviation of 8.84 percent. The Covid-19 distribution page is 70.36 percent usable, with a standard deviation of 9.84 percent. The evaluation results are based on the United States' Research-Based Web Design and Usability Guidelines. The Department of Health and Human Services (HHS) discovered that the home page's links were poorly identified, that important information was not relevant, and that the use of icons was inconsistent. The distribution page discovered difficult-to-identify links, scrollbar redundancy in the frameset, and content complexity that required the user to be able to read diagrams well.